THE DEFORMATION ASPECT OF SHOCK-WAVE NATURE OF FRICTION AND WEAR - Malinovskiy, Yuriy; Tsvirkun, Sergij; Vlasenkov, Dmitro; Oliinyk, Svitlana (Problems of Friction and Wear, 2023)
As statistical analysis shows, the main reason for the failure of machines is not their destruction, but the wear of moving joints and working bodies under the influence of frictional forces. However, when creating machines, the movable joint is practically not calculated in terms of resistance to wear. At the same time, there are the following methods of tribotechnical calculation, and they are based on the following groups of theories: geometric; molecular, deformation and combined. All these theories consider processes occurring at contact surfaces. In addition, the currently used approach does not take into account the peculiarities of the deformation processes occurring in front of the mobile part. At the same time, the mobile part (stamp) «accelerates» the wave of deformation of the «launch» on the fixed part, which, as a rule, is not taken into account when considering the processes of friction and wear. We note that these deformation processes during friction and wear are due to shear deformations in front of the moving stamp, and despite established ideas, the hypothesis of flat sections is distorted, as a result of which deformation waves appear on the outer surfaces of the half-spaces. In other words, the displaced layers are not able to move freely along the shear plane, while the so-called «confined shear» occurs, which leads to the deplaning of the outer and inner planar sections. With this view of the matter, the surface layer of the half-space either loses its longitudinal stability or is subjected to cyclic stresses. In both cases, wear and intense scratching of the contact surfaces occurs. In addition, with the interaction of the die (or micro-irregularities formed on it) with the micro-irregularities of the strip in both interacting parts, a continuous wave process is established. Note that with an increase in the die speed V, the dynamic coefficient of the system changes in proportion to the change in the die speed. The research made it possible to establish that for the stable operation of the surface layers of the beam-strip it is necessary that the value of the longitudinal (critical) force overload coefficient is less than the number of half-waves of deformation formed in front of the moving die. In addition, it was established that the deformation-wave processes that occur in front of the moving die lead to the formation of permanent plastic or elastic ridges, which are obstacles for the moving die, and these obstacles are interpreted in the differential equations of motion as impulse loads. The obtained results indicate that elements of both the deformation-wave and shock-wave theories of friction and wear are manifested during the interaction of moving parts. The application of the specified approach makes it possible to clarify the calculation methods for friction and wear both in the case of deformation and in the case of geometric micro-uniformities.